55.9k views
5 votes
If f(x)=x⁴-x³+x² and g(f)=-x², where x can not equal 0, what is (f/g)(x)?

User Karan K
by
5.5k points

1 Answer

3 votes

Answer:


\displaystyle ((f)/(g))(x) = -(x^2 - x + 1)

General Formulas and Concepts:

Algebra I

  • Terms/Coefficients
  • Factoring
  • Functions
  • Function Notation

Explanation:

Step 1: Define

Identify


\displaystyle f(x) = x^4 - x^3 + x^2


\displaystyle g(x) = -x^2

Step 2: Find

  1. Substitute in function values:
    \displaystyle ((f)/(g))(x) = (x^4 - x^3 + x^2)/(-x^2)
  2. Factor:
    \displaystyle ((f)/(g))(x) = (x^2(x^2 - x + 1))/(-x^2)
  3. Simplify:
    \displaystyle ((f)/(g))(x) = -(x^2 - x + 1)
User Kerry Liu
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.